Antimicrobial Resistance in Escherichia coli Isolates from Healthy Poultry, Bovine and Ovine in Tunisia: A Real Animal and Human Health Threat - Mohamed Salah Abbassi; Hajer Kilani; Mohamed Zouari; Riadh Mansouri; Oussama El Fekih; Salah Hammami; Noureddine Ben Chehida (Journal of Clinical Microbiology and Biochemical Technology - Peertechz Publications, 2017)
A total of 174 E. coli isolates collected from healthy poultry, bovine and ovine recovered between December 2009 and June 2013 in different geographic location in Tunisia, were assessed and examinated for resistance to antimicrobial agents. Avian isolates showed the highest rates of antibiotic resistance: tetracycline (74.7 %), trimethoprim/sulfamethoxazole and amoxicillin with the same rate of resistance (57 %). Prevalences of resistance to the same four antimicrobials in bovine isolates were 33.3 %, 65 %, 30 %, 28.3 %, respectively. However, for ovine isolates, low resistance rates were observed, except for tetracycline (40 %) and amoxicillin (22.85 %). Only one ESBL-producing isolate from chicken was detected. In addition, seventy-seven (44.2 %) isolates were resistant to three or more classes of antibiotics and were considered multidrug resistant (MDR). Interestingly, avian E. coli isolates were more resistant than bovine and ovine ones. These results provide novel insights into the epidemiological characteristics of poultry, bovine and ovine E.coli isolates in Tunisia, and suggest the need for the prudent use of antimicrobial agents in husbandry and the urgent need to establish a national antibiotic resistance monitoring program.